Peer Interaction in Enhancing Students' Motivation to Learn English Among Gen Z University Students - Ratu Tri Anisa; Musdizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the role of peer interaction in enhancing English learning motivation among Generation Z students at the English Language Education Program of Institut Agama Islam Negeri (IAIN) Kerinci. This study employed a qualitative approach using semi-structured interviews with four students selected through purposive sampling. The data were analyzed using thematic analysis to explore how peer interaction influenced students’ motivation in learning English. The findings showed that peer interaction strengthened both intrinsic and extrinsic motivation through collaborative discussions, emotional support, academic encouragement, and positive social relationships among students. These interactions increased students’ self-confidence, active participation, and enthusiasm in learning English while also creating a supportive and comfortable learning environment. The study concludes that peer interaction plays a significant role in sustaining Generation Z students’ motivation to learn English in higher education contexts. Keywords: English learning, Generation Z, Higher education, Learning motivation, Peer interaction.